2007
DOI: 10.1042/bj20070177
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino acid residues at the active site of endosialidase that dissociate the polysialic acid binding and cleaving activities in Escherichia coli K1 bacteriophages

Abstract: Endosialidase (endo-N-acetylneuraminidase) is a tailspike enzyme of bacteriophages specific for human pathogenic Escherichia coli K1, which specifically recognizes and degrades polySia (polysialic acid). polySia is also a polysaccharide of the capsules of other meningitis- and sepsis-causing bacteria, and a post-translational modification of the NCAM (neural cell-adhesion molecule). We have cloned and sequenced three spontaneously mutated endosialidases of the PK1A bacteriophage and one of the PK1E bacteriopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 44 publications
1
34
1
Order By: Relevance
“…It has also been shown that endoNF preferentially binds sialic acid oligomers in this helical form (85), and the enzyme could provide the second acid or base catalyst, normally required in a glycosidase mechanism, to further increase the rate of depolymerization. This is consistent with the observation that amino acid changes around the putative active site of endo-sialidases drastically change the catalytic efficiency, by locally distorting the polymer in a way that does not promote transition state formation but does not affect binding of the polymer, because there are multiple sugar-binding sites (48).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It has also been shown that endoNF preferentially binds sialic acid oligomers in this helical form (85), and the enzyme could provide the second acid or base catalyst, normally required in a glycosidase mechanism, to further increase the rate of depolymerization. This is consistent with the observation that amino acid changes around the putative active site of endo-sialidases drastically change the catalytic efficiency, by locally distorting the polymer in a way that does not promote transition state formation but does not affect binding of the polymer, because there are multiple sugar-binding sites (48).…”
Section: Discussionsupporting
confidence: 77%
“…This mutant was shown to be properly folded and capable of binding substrate but showed no sialidase activity toward the sialotrioside substrate under a range of conditions. This is not entirely unexpected because recent studies on other endo-sialidases have shown that other mutations around the putative active site can have a drastic effect on catalysis without affecting binding (48). The complete ablation of sialidase activity, however, is in apparent contrast to previous studies of the E581A mutant, in which a 5% residual sialidase activity was observed (15).…”
Section: Discussioncontrasting
confidence: 54%
“…Five endosialidase genes have been cloned from different E. coli K1 bacteriophages (7)(8)(9)(10)(11)(12)(13). The proteins encoded by these genes share a common architecture with three linearly organized domains as follows.…”
mentioning
confidence: 99%
“…Yellow residues have been described to be directly involved in catalysis [106,127] whereas green amino acids have been mutated and identified as polysialic acid binding residues [12,106]. Blue colored residues have been identified in inactive endoNA or endoNE mutants [15,69] enzymatic activity [106]. Further residues were identified by natural mutation of the endosialidases from K1A and K1E to be important for catalysis (depicted in blue in Fig.…”
Section: The Active Site Of Endosialidasementioning
confidence: 98%
“…Further residues were identified by natural mutation of the endosialidases from K1A and K1E to be important for catalysis (depicted in blue in Fig. 3c; [69], see Sect. 12.1).…”
Section: The Active Site Of Endosialidasementioning
confidence: 99%